2010
DOI: 10.1002/chem.200903580
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanine–Polyamine Conjugates as pH‐Controlled Photosensitizers for Photodynamic Therapy

Abstract: A series of aryl hydroxyamines prepared by reductive amination were treated with silicon(IV) phthalocyanine dichloride in the presence of pyridine to give the diaxially substituted phthalocyanine-polyamine conjugates 1-5. The electronic absorption, fluorescence emission, and efficiency at generating reactive oxygen species of these compounds were all sensitive to the pH environment. Under acidic conditions, the fluorescence quantum yields and the singlet oxygen quantum yields of these compounds were greatly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(36 citation statements)
references
References 62 publications
1
34
0
Order By: Relevance
“…Similar work by Ng and co-workers has also shown great success in using polyamines as the axial ligands. [18,19] The addition of these axial ligands not only improves solubility, but also hinders the formation of larger aggregates, which are typical of planar aromatic molecules in unfavorable solvation conditions. [20] The important relationship between Pc 4's chemical structure and photophysics is highlighted by the results of Foster and co-workers, who found that after PDT the fluorescence from the SiPc 4 drug increased.…”
Section: Introductionmentioning
confidence: 99%
“…Similar work by Ng and co-workers has also shown great success in using polyamines as the axial ligands. [18,19] The addition of these axial ligands not only improves solubility, but also hinders the formation of larger aggregates, which are typical of planar aromatic molecules in unfavorable solvation conditions. [20] The important relationship between Pc 4's chemical structure and photophysics is highlighted by the results of Foster and co-workers, who found that after PDT the fluorescence from the SiPc 4 drug increased.…”
Section: Introductionmentioning
confidence: 99%
“…[13,26] Amino groups also provoke ap H-dependent quenching of Pc excited states. [27,28] Yet, from al ogical perspective, in both cases, 1 O 2 productiona nd SiPc fluorescencea re recovered simultaneously.T hus, these systems present only as ingle combinedo utput signal and, therefore, al imited capacity for molecular computing.…”
mentioning
confidence: 89%
“…The first strategy is to promote the selective accumulation of the photosensitiser into tumorous tissues by conjugating it to tumour-targeting moieties [6], or the administration of photosensitiser under a photo-inactive form going to be activated only in the specific tumour conditions. In this later case, the activation should be induced thanks to the tumour specific conditions, hence based on the more elevated temperature [7] of tumorous tissues, on their acidity [8], on their reductive character due to the elevated concentration of glutathione [9] or thanks to the presence of tumour-specific enzymes [10]. Such systems are called photo molecular beacons.…”
Section: Introductionmentioning
confidence: 99%